Clinical Applications of CO2 and H2 Breath Test - ZHAO Si-qian;CHEN Bao-jun;LUO Zhi-fu (Journal of Isotopes, 2016)
Breath test is non-invasive, high sensitivity and high specificity. In this article, CO2 breath test, H2 breath test and their clinical applications were elaborated. The main applications of CO2 breath test include helicobacter pylori test, liver function detection, gastric emptying test, insulin resistance test, pancreatic exocrine secretion test, etc. H2 breath test can be applied in the diagnosis of lactose malabsorption and detecting small intestinal bacterial overgrowth. With further research, the breath test is expected to be applied in more diseases diagnosis.